ANALISIS RISIKO USAHA PEMBIBITAN KARET DI DESA PONDOK MEJA KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Malik, Adlaida; Fitri, Yanuar; Herdiyansyah, Rikky (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
Risk is a variation about the things that might occur naturally or the possibility of the event that might happen unexpectedly which include as the threat of business and finansial profit due to danger occured. This study aims to: 1) to know risk sources that influence rubber breeding business, 2) to know how much risk probability on rubber breeding business and 3) to evaluate the risk include in rubber breeding business at Desa Pondok Meja Kecamatan Mestong Kabupaten Muaro Jambi. This research conducted on August 27th 2015 to September 27th 2015 toward 20 rubber seed farmer. The method used is descriptive quantitative analysis, by analysing probability and z-score value. Next, do analysis to evaluate business by calculating the expected return, variety, standard deviation, coefficient of variation and lower limit revenue. Descriptive analysis indicates that risk sources in rubber breeding business at research site exsist on production aspect, price or market and human or individual. From probability analysis result obtained the highest probability happened in production aspect caused by mortality (die of seed). Standard deviation values obtained by Rp. 10.163.469,93 which shows that this rubber breeding has a not high risks. On coefficient variation and lower limit revenue value obtained by 0,1857 and Rp. 34.393.911,14/Year. Coefficient variation value is less than 0,5 and lower limit revenue value is higher than 0. Evaluation result indicate that this rubber breeding will not face losses opportunities (no risk) in every breeding period by minimizing the risk chance that will occur.